A CFD analysis of NACA 0015 airfoil as a horizontal stabilizer with gap length variations - Gunawan Nugroho; Herman Sasongko; Mohammad Adenan; Sarwono; Heru Mirmanto (Journal of Energy, Mechanical, Material, and Manufacturing Engineering, 2022)
The horizontal stabilizer is an important device which stabilize in the longitudinal direction is an important device for aviation. It also controls the pitching nose through the variation of elevator deflection angle. This work is to relate the lift coefficient with elevator deflection angle. The applied horizontal stabiliser is a plain flap with the gap length of 1.75%, 2% and 2.25% w.r.t. chord length. Results show that higher elevator deflection angle increases lift coefficient. For the 2 degree angle of attack and 20 degree of elevetor deflection angle, the lift coefficient is 0.93 (gap length 1.75%). Moreover, the lift coefficient is 1.83 for 10 degree horizontal stabiliser (gap length 2%).